Tipologia de instituição de longa permanência e de centro dia para idosos segundo a visão de seus gestores - Corsini, Tatiana de Vasconcellos Melo (Universidade Federal de São Carlos, 2019)
Introduction: The necessity of increasing resources and care support networks to attend the elderly population becomes emergent every year, due to the accelerated growth of the elderly in Brazil. Chronical diseases, functional limitations, increased longevity and the failure of families to offer appropriate support are present in population ageing. At some point in the old age, the necessity of daily care is real. Family is the first to offer this care, as well as some community spaces that give the support and care based on public policy, among which the Long-Term Care Institutions for Elders (ILPI) and the Senior Day Care Centers (CDI). Objective: Verify the comprehension of the managers of the ILPI that also have CDI in two towns (Araraquara and São Carlos) of the state of São Paulo, about the typology of these services. Methodology: This research is exploratory, descriptive and qualitative and quantitive study. It was carried out in the ILPI of São Carlos and Araraquara. Part of the data were collected on a database of the research group involved, followed by the application of a semi structured questionnaire with the managers of the ILPI that also have CDI services. A simple statistical analysis, descriptive, by means of frequency and percentage, as well as the construction of categorical variables through the content analysis was applied as well as the ethical care. Results: There are 26 ILPI, 21 private and 5 philanthropic. They have 833 vacancies, of which 712 are occupied, mostly by women (68%). The routine is determined by activities in the area of feeding, personal care and medication control. Among the 26 ILPI, 16 offered CDI services. Their managers are 11 women and 5 men, 44 years old on average and connected to the ILPI for 2.6 years. Of these, 11 have higher education with a predominance of nursing degrees (5) and business administration (4). Four managers pointed out that the services should have distinct planning, even though the 16 ILPI use the same structure, routine and staff. Conclusion: The managers' vision about the typology of the services seems to be mistaken, performing it without specific technical standards.
Tipology of long-term care institutions for elders and senior day care centers according to the view of their managers
Keywords: Gerontologia; Instituição de longa permanência para idosos; Proteção social; Assistência diurna; Idoso; Gerontology; Long-term care institutions for elders; Social protection; Day care; Elder; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; CIENCIAS DA SAUDE::SAUDE COLETIVA